The Factors of Job Satisfaction Among Nurses - Intan Julia Anastasia; I Gede Putu Darma Suyasa; IGN Made Kusuma Negara; Made Dian Shanti Kusuma (Babali Publisher, 2023)
Introduction: Hospital as health service center must really pay attention to the importance of health services to patients that rely on human resources. Job satisfaction among nurses is one of the factors that contribute to maintaining the quality of health services. As health workers who are directly involved in providing care to patients, nurses have a very strategic role in meeting patient needs and creating a safe, comfortable, and effective care environment. Methods: Research uses an analytical survey design with a cross sectional approach. The population was all 559 nurses. The number of samples was 233, using the proportional sampling method. Data collection using questionnaires, has been tested for validity and reliability test with r value above 0.361. Analysis techniques using chi-square and binary logistic regression analysis. Results: Perception of the nursing manager leadership variable shows an average value of 2.31, which means that the nursing manager leadership is good category. Based on the Chi-Square results, it is known that nursing manager leadership, social support, work family conflict, have a significant relationship with nurse job satisfaction with a p value ≤0.05. Meanwhile, the gender variable does not have a significant relationship with nurses job satisfaction with p value> 0.05 Multivariate analysis with ordinal regression test shows that social support with a p value = 0.00 <0.25 and Wald (OR) value of 15.856 is the largest. Conclution: There is a significant relationship between leadership and job satisfaction of nurses and there is also a significant relationship between social support and job satisfaction of nurses. Keywords: Job Satisfaction, Manager, Leadership, Social Support, Nurses